A Randomized, Rater-Blinded, Crossover Study of the Effects of Oxymorphone Extended Release, Fed versus Fasting, on Cognitive Performance as Tested with CANTAB in Opioid-Tolerant Subjects. Issue 2 (13th February 2014) - Spierings, Egilius L. H.; Volkerts, Edmund R.; Heitland, Ivo; Thomson, Heather
Abstract: Background: The maximum plasma concentration (Cmax ) of oxymorphone extended release (ER) 20 mg and 40 mg is approximately 50% higher in fed than in fasted subjects, with most of the difference in area-under-the-curve (AUC) occurring in the first 4 hours post-dose. Hence, the US FDA recommends in the approved labeling that oxymorphone ER is taken at least 1 hour before or 2 hours after eating. Methods: In order to determine the potential impact on cognitive performance of the increased absorption of oxymorphone ER, fed versus fasting, we conducted a randomized, rater-blinded, crossover study in 30 opioid-tolerant subjects, using tests from the Cambridge Neuropsychological Test Automated Battery (CANTAB). The subjects randomly received 40 mg oxymorphone ER after a high-fat meal of approximately 1, 010 kCal or after fasting for 8–12 hours, and were tested 1 hour and 3 hours post-dose. Results: The CANTAB tests, Spatial Recognition Memory (SRM) and Spatial Working Memory (SWM), showed no statistically significant differences between the fed and fasting conditions. However, sustained attention, as measured by the Rapid Visual Information Processing (RVP) CANTAB test, showed a statistically significant interaction of fed versus fasting and post-dose time of testing ( F [1, 28] = 6.88, P = 0.01), suggesting that 40 mg oxymorphone ER after a high-fat meal versus fasting mitigates the learning effect in this particular cognition domain from 1 hour to 3 hours post-dose. Conclusion: Oxymorphone 40 mg ER affected cognitive performance similarly within 3 hours post-dose, whether given on an empty stomach or after a high-fat meal, suggesting that the effect of food on plasma concentration may not be relevant in the medication's impact on cognition.